Sustainable aviation futures - Budd, Lucy; Griggs, Steven; Howarth, David (Transport and sustainability, 2013)
This volume brings together some of the leading names in global aviation policy research to provide a unique and ground breaking synthesis of current debates on sustainable aviation. Unlike previous edited works, this volume is inter-disciplinary and international in nature, drawing on the work of social scientists, transport specialists, and policy experts working in the domains of academia, direct action, and regulation to inform understandings of the prospects for sustainable aviation. Uniquely, the title explores the context of the challenge and examines both scenarios and coalitions for change.